Hypercritical or Superficial? Investigating the Metacognitive Awareness of Indonesian Bilingual Students in Writing Class - Melti Oktavianda; Sistiadinita (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2025)
Metacognition has long touched upon critical issues related to educational psychology and gained advancing recognition in language learning. However, empirical research on its effect on academic writing remains limited. This study investigated metacognitive awareness among 167 Indonesian university students enrolled in an academic writing class, focusing on two self-assessment patterns: superficial (overestimating abilities) and hypercritical (underestimating abilities). Using an explanatory sequential mixed methods design, the researchers first compared students' actual writing exam scores with their self-assessments, which mirrored the lecturer’s grading rubric. Students were grouped into quartiles based on performance, and a Wilcoxon Signed Rank Test was conducted to examine differences between their actual and perceived scores. Results revealed distinct patterns. Among lower-performing students (bottom quartile), only 11 out of 53 students (approximately 21%) exhibited superficial self-assessment. In contrast, among higher-performing students (top quartile), 61 out of 63 students (97%) demonstrated hypercritical self-assessment. These results suggest that while only a minority of low-performing students were superficial, the majority of high-performing students tended to be hypercritical about their writing abilities. Follow-up interviews with four selected students further explored the reasons behind these patterns. Qualitative analysis identified three main contributing factors: person and task variables, response to feedback, and self-regulation strategies. The findings underscore the importance of fostering metacognitive awareness and accurate self-assessment in foreign language writing instruction to promote effective learning and self-regulated development.